Antibiogram and biofilm formation among extended-spectrum ?-lactamase-producing Klebsiella pneumoniae clinical isolates in Sanglah General Hospital, Bali, Indonesia - Ichlazul Ma’ruf; Made Agus Hendrayana; I Dewa Made Sukrama; Ni Nengah Dwi fatmawati (DiscoverSys Inc., 2021)
Background: Klebsiella pneumoniae is a common cause of healthcare-associated infections (HAIs), and has a high level of resistance to antibiotics first, second, extended-spectrum cephalosporins, and monobactam which are a serious threat to public health worldwide. Besides, it is known that this bacterium can form biofilms as virulence factors that contribute to drug resistance. This study aims to determine the antibiotics susceptibility patterns and the capacity of K. pneumoniae to form biofilms.Methods: K. pneumoniae was isolated from clinical specimens (urine, sputum, pus, blood, and others) for the period 2018-2019. Bacterial identification and antibiotic susceptibility testing were performed using the Vitek Compact 2 (bioMérieux®) test in the Clinical Microbiology Laboratory of Sanglah General Hospital. Biofilm formation was checked using the tissue culture plate method (TCP). Data were analyzed using SPSS version 20 for Windows.Results: Most of Extended Spectrum ?-Lactamase (ESBL)-producing K. pneumoniae showed resistance to antibiotics. The susceptible profiles were only towards ertapenem (97.50%), meropenem (97.50%), amikacin (95.00%), and tigecycline (87.50%). The TCP method detected 72 (90.00%) as biofilm producers among 80 clinical isolates, while 8 (10.0%) as non-biofilm producers. Among the biofilm-producer bacteria, there were 6 (7.50%) as strong, 37 (46.25%) moderate, and 29 (36.25%) weak biofilm-producer isolates.Conclusions: Most ESBL-producing K.pneumoniae clinical isolates in Sanglah General Hospital demonstrate multiple resistance to antibiotics and as biofilm producers. However, further research is needed to be conducted using a molecular approach to see the ESBL- and biofilm-encoded genes.